Synthesis and Biological Activity of New Antifungal Compounds: A Preliminary Study - Cabezas Pizarro, Jorge A. (2018)
In the present study, we synthesized three 1,3-enynes from their corresponding aldehydes. They exhibited antifungal activity, which was evaluated against Trichophyton rubrum, the most common dermatophyte responsible for nail infection. The biological activity of these synthetic enynes was compared to terbinafine and ciclopirox olamine, two common antimycotic drugs used to treat nail infections caused by this pathogen. Two of these compounds showed an inhibitory effect similar to terbinafine and cilopirox olamine, when tested against over eleven different T. rubrum strains, including ATCC 28188 strain and ten different clinical isolates, two already classified as multitreated.